Female circumcision. Universal prohibition or uncritical acceptance: somewhere in between? - Decarli, Giorgia (Antropologia Pubblica, 2024)
The essay provides insights to further emphasize the importance of an alternative conceptualization of female circumcision that could overcome the still unsolved conundrum of a legislative ban that potentially perpetuates gender inequality. While law condemns the practice as a form of violence against women, the number of circumcisions does not drastically decline. In addition, we witness several women and girls wanting to undergo female circumcision: a phenomenon that some activists (and some scholars) attempt to portray in the wider frame of the right to self-determination and cultural identity. Hence, questions arise as to what alternatives can be recommended other than universal prohibition or uncritical acceptance.